Exploring therapeutic applications of PTEN, TMPRSS2:ERG fusion, and tumour molecular subtypes in prostate cancer management - Bugoye, Fidelis Charles; Torrorey-Sawe, Rispah; Biegon, Richard; Dharsee, Nazima; Mafumiko, Fidelice; Kibona, Herry; Aboud, Said; Patel, Kirtika; Mining, Simeon (Frontiers in Oncology, 2025)
BackgroundProstate cancer is defined by the suppression of genes that suppress tumours and the activation of proto-oncogenes. These are the hallmarks of prostate cancer, and they have been linked to numerous genomic variations, which lead to unfavourable treatment outcomes. Prostate cancer can be categorised into various risk groups of tumour molecular subtypes grounded in the idea of genomic structural variations connected to TMPRSS2:ERG fusion and loss of PTEN. Research suggests that certain genomic alterations may be more prevalent or exhibit different patterns in prostate cancer tumours across populations. Studies have reported a higher frequency of PTEN loss and TMPRSS2:ERG fusion in prostate tumours of Black/African American men, which may contribute to the more aggressive nature of the disease in this population. Thus, therapeutically important information can be obtained from these structural variations, including correlations with poor prognosis and disease severity.MethodsPeer-reviewed articles from 1998 to 2024 were sourced from PubMed and Google Scholar. During the review process, the following search terms were employed: “Tumour suppressor genes OR variations OR alterations OR oncogenes OR diagnostics OR ethnicity OR biomarkers OR prostate cancer genomics OR prostate cancer structural variations OR tumour and molecular subtypes OR therapeutic implications OR immunotherapy OR immunogenetics.”ResultsThere was a total of 13,012 results for our search query: 5,903 publications from Google Scholar with the patent and citation unchecked filer options, and 7127 articles from PubMed with the abstract, free full text, and full-text options selected. Unpublished works were not involved. Except for four articles published between 1998 and 1999, all other selected articles published in 2000 and later were considered. However, papers with irrelevant information or redundant or duplicate content were not chosen for this review. Thus, 134 met the inclusion criteria and were ultimately retained for this review.ConclusionThis review extracted 134 relevant articles about genomic structure variations in prostate cancer. Our findings demonstrate the importance of PTEN and TMPRSS2:ERG fusion and tumour molecular subtyping in prostate cancer precision medicine.